The Importance of the Entrepreneur’s Soul in the State Civil Apparatus - M. Widaningsih; Novianita Rulandari (Yayasan Ilomata, 2022)
The task of the State Civil Apparatus as mandated in the Act is to provide good service to the community, therefore it is very important if the State Civil Apparatus has an entrepreneurial spirit in providing services to the community, so that the services provided have the characteristics of fast and timely service. But in reality, the public services that we meet in the community still have a very long bureaucratic span, because one of them is related to the characteristics of human resources than the ASN who still do not have an understanding of the competencies they have. The method used in this paper is by taking data based on literature reviews from various sources relating to what is studied in this paper and describing some findings that describe the slowness of public services in one area in West Java. The san that becomes an obstacle for ASN still has an entrepreneurial spirit because it collides with some old rules that have been entrenched, so that it has an impact on the weak characteristics of the ability of the State Civil Apparatus in providing public services to the community.